THE INFLUENCE OF THE FUNCTIONS OF LAW ON THE FORMATION OF THE LEGAL CULTURE OF THE PERSON AND UKRAINIAN SOCIETY - Pilgun, Nataliia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: research of topical issues of the influence of the functions of law on the formation of the legal culture of the individual and society. Achieving this goal is ensured by defining the concept of legal functions, understanding the legal culture of society and the individual, as well as the specifics of legal functions and their impact on the formation of legal culture and reform of the legal system of Ukraine. The methodological basis of the work is a comprehensive approach to the analysis of the functions of law on the formation of legal culture. It is based on the dialectical method of research, the method of historicism and comparison, the intersectoral method of legal research, formal-logical and logical methods that have been used as tools to achieve this goal. Results: as a result of scientific research the connection of purpose of functions of the right with directions of their influence and vice versa is established. Discussion: revealing the content of legal functions and their impact on the formation of legal culture of the individual and society, emphasis is placed on the fact that the social purpose of law is determined by the needs of social development, which creates a regulatory framework aimed at It is concluded that the direction of influence is the most important component of the functions of law, which are a kind of response to the needs of social development. As for the legal influence, which characterizes the ways, forms and ways of influencing public relations and the level of legal culture of the individual and society, it is the implementation of legal principles, guidelines, prohibitions, regulations and norms in public life, activities of states, its bodies, public unions and citizens. As a result of the study, it was determined that the forms of legal influence include: informational, psychological, educational and social. Today the problem of formation and functioning of the functions of law in solving global problems of today, which characterize not only the level of legal culture of the individual, but also society. Strengthening the regulatory potential of legal culture is, first of all, strengthening the normative basis of both law and morality, deepening the morality of law, expressing in law and morality the principles of justice, humanism, protection of human rights, which unites law and morality. Identification and implementation of regulatory reserves of legal culture involves the use of value-regulatory, regulatory capabilities of both law and its functions and morals and create conditions for their mutual enrichment, strengthening the impact on society.